Pre-pregnancy BMI and intake of energy and calcium are associated with the vitamin D intake of pregnant Malaysian women - Yong, Heng Yaw; Zalilah, Mohd Shariff; Tan, Choi Wan; Koo, Shi Jia (Family Medicine & Primary Care Review, 2017)
Background . Adequate vitamin D intake during pregnancy is important for prevention of adverse pregnancy outcomes. Objectives . The present study aims to determine the intake and sources of vitamin D, as well as factors associated with vitamin D intake among pregnant Malaysian women. Material and methods . This cross-sectional study was conducted at the Seremban Maternal and Child Health (MCH) clinic, Negeri Sembilan. Women (n = 314) were measured for height and weight and interviewed for socio-demographics, obstetrics, dietary intake, source of vitamin D, intake of vitamin D supplements and physical activity. Results . One-third of pregnant women were overweight (21%) or obese (13%) with a mean pre-pregnancy Body Mass Index (BMI) of 23.65 ± 5.29 kg/m². The mean vitamin D intake of pregnant women was 11.54 ± 0.45 μg/day (diet = 6.55 ± 4.43 μg/day; supplements = 4.99 ± 5.95 μg/day) with approx. 74.5% of intake being above recommendation levels. Milk and milk products showed the greatest contribution to vitamin D intake (56.8%). While women with higher energy (adjusted OR = 0.10, 95% CI = 0.01–0.87) and calcium (adjusted OR = 0.27, 95% CI = 0.11–0.67) intake were more likely to have adequate vitamin D intake, obese women were less likely to have adequate vitamin D intake (adjusted OR = 1.65, 95% CI = 1.72–3.79). Conclusions . Adequate intake of vitamin D was significantly associated with higher energy and calcium intake, but obese women tend to have inadequate intake. Further studies need to confirm these finding and the contribution of vitamin D intake to vitamin D status in pregnant Malaysian women.